Analytical method development and occurrence of microplastics from daily food containers - Chan, Jasmine Qiu Rong (Nanyang Technological University, 2020)
With the emerging concern of microplastics accumulation in the environment, a plethora of studies have investigated the occurrence of microplastics in natural water bodies, atmosphere and various food products such as salt, seafood, honey and more. These amount to humans ingesting an alarming estimation of 5 grams of plastics per week (World Wide Fund for Nature (WWF), 2019). With the numerous analytical equipment available for the study of microplastics, this report explores the optimisation of these analytical equipment such as colour identification for the different types of plastics using a fluorescence microscope and pyrolysis gas chromatography mass spectrometry (Py-GCMS) to detect microplastics of smaller micron size. An optimal pyrolysis temperature and time of 600 degC and 60 seconds for Py-GCMS of synthetic polymers, specifically polystyrene (PS), was proposed. Furthermore, the limit of detection (LOD) and limit of quantitation (LOQ) of PS were further improved using the characteristic breakdown compounds of PS: styrene, styrene dimer and styrene trimer under a single ion monitoring (SIM) method in Py-GCMS. This results in the minimum detection of 0.889 mg/L, 5.58 mg/L and 14.7 mg/L for styrene, styrene dimer and styrene trimer respectively. Whereas, limit of quantitation is 2.69 mg/L, 16.9 mg/L and 44.4 mg/L for styrene, styrene dimer and styrene trimer respectively. With the majority of studies focusing on microplastics in water bodies, there is a lack of studies on the other possible sources of microplastics and its pathways into human exposure. In this report, the occurrence of microplastics from commonly used daily food containers for takeaway services were also investigated using the optimised analytical methods. Results from Py-GCMS and scanning electron microscopy (SEM) imaging showed a potential of microplastics leaching from a PS clam shell container into the container’s contents when subjected to scraping with utensils or high temperatures. By using the fluorescence and confocal microscope, approximately 153 particles per mL were estimated to leach out of a PS clam shell container that contained 100 mL 95 degC water, suggesting a possible substantial source for human microplastic exposure.